The Dorsoventral Patterning of Human Forebrain Follows an Activation/Transformation Model. (25th May 2016) - Chi, Liankai; Fan, Beibei; Feng, Dandan; Chen, Zhenyu; Liu, Zhongliang; Hui, Yi; Xu, Xiangjie; Ma, Lin; Fang, Yujiang; Zhang, Quanbin; Jin, Guohua; Liu, Ling; et al.
Abstract: The anteroposterior patterning of the central nervous system follows an activation/transformation model, which proposes that a prospective telencephalic fate will be activated by default during the neural induction stage, while this anterior fate could be transformed posteriorly according to caudalization morphogens. Although both extrinsic signals and intrinsic transcription factors have been implicated in dorsoventral (DV) specification of vertebrate telencephalon, the DV patterning model remains elusive. This is especially true in human considering its evolutionary trait and uniqueness of gene regulatory networks during neural induction. Here, we point to a model that human forebrain DV patterning also follows an activation/transformation paradigm. Human neuroectoderm (NE) will activate a forebrain dorsal fate automatically and this default anterior dorsal fate does not depend on Wnts activation or Pax6 expression. Forced expression of Pax6 in human NE hinders its ventralization even under sonic hedgehog (Shh) treatment, suggesting that the ventral fate is repressed by dorsal genes. Genetic manipulation of Nkx2.1, a key gene for forebrain ventral progenitors, shows that Nkx2.1 is neither necessary nor sufficient for Shh-driven ventralization. We thus propose that Shh represses dorsal genes of human NE and subsequently transforms the primitively activated dorsal fate ventrally in a repression release manner.